Digital transformation in the use of artificial intelligence in education for smart schools in Jenin Governorate - Abu Farhah, Inas Fuad; Abu Farhah, Maher Fuad (Journal of Educational and Psychological Sciences, 2024)
The study aimed to identify the degree to which teachers in Jenin Directorate possess digital learning skills using artificial intelligence in education, as well as their attitudes regarding its use, and the extent to which there are statistically significant differences at the significance level (α≤0.05) in the sample's perspectives attributed to the variables of gender and experience. The descriptive analytical method was utilized, along with a questionnaire consisting of 20 items, which was distributed to a stratified random sample of (289) teachers in schools within Jenin Governorate. The results of the study indicated a limited availability of modern technologies in Palestinian schools and a weak internet infrastructure, in addition to a lack of benefit for faculty members from technological and informational advancements, which led to a decline in the level of digital transformation in Palestinian schools. Based on these results, the researcher recommended enhancing teacher training programs with educational units focused on digital learning, the use of technology, and artificial intelligence in teaching and learning, as well as organizing training courses for teachers to keep up with developments in this field.
Keywords: Digital Transformation; Artificial Intelligence; Education; Smart Schools; Palestine